2009
DOI: 10.1177/0022034509341967
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Purine Degradation by Periodontal Diseases

Abstract: Periodontal diseases, such as gingivitis and periodontitis, are characterized by bacterial plaque accumulation around the gingival crevice and the subsequent inflammation and destruction of host tissues. To test the hypothesis that cellular metabolism is altered as a result of host-bacteria interaction, we performed an unbiased metabolomic profiling of gingival crevicular fluid (GCF) collected from healthy, gingivitis, and periodontitis sites in humans, by liquid and gas chromatography mass spectrometry. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
107
1
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(136 citation statements)
references
References 22 publications
14
107
1
12
Order By: Relevance
“…These results were consistent with the findings of Mazumdar et al (2009), in which computational construction and analysis of the genome-scale metabolic network of P. gingivalis were employed. Even though the relative abundance of three genes involved in glycolysis was increased and that of the other two genes was decreased in periodontitis samples, the alteration of maltose, glucose, fructose and xylose metabolism genes was not evident, and this disagrees with other studies carried on saliva, gingival crevicular fluid and single pathogenic bacterium P. gingivalis Strain W83 (Nelson et al, 2003;Barnes et al, 2009Barnes et al, , 2011.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…These results were consistent with the findings of Mazumdar et al (2009), in which computational construction and analysis of the genome-scale metabolic network of P. gingivalis were employed. Even though the relative abundance of three genes involved in glycolysis was increased and that of the other two genes was decreased in periodontitis samples, the alteration of maltose, glucose, fructose and xylose metabolism genes was not evident, and this disagrees with other studies carried on saliva, gingival crevicular fluid and single pathogenic bacterium P. gingivalis Strain W83 (Nelson et al, 2003;Barnes et al, 2009Barnes et al, , 2011.…”
Section: Discussioncontrasting
confidence: 82%
“…The increased peptides and amino acids would supply as a richer energy pool for the expansion of some specific organisms relying on oligopeptides as carbon and energy sources (Takahashi and Sato, 2002) that ultimately influences the microbial and functional structure. In the present study, genes encoding lysine decarboxylase, L-alanine dehydrogenase, biosynthetic arginine decarboxylase PLP-binding and argininosuccinate lyase exhibited a higher abundance in periodontitis that might lead to the increasing of many amino acid metabolites in periodontal patients (Barnes et al, 2009(Barnes et al, , 2011. Among the genes involved in amino acid synthesis with distinct abundance, 15 out of 19 genes showed lower relative abundance in periodontitis, indicating that subgingival community of periodontal group might utilize some ammonia absorbed directly for physiological activities instead of biosynthesizing themselves.…”
Section: Discussionmentioning
confidence: 53%
“…Acceleration in purine degradation and increased oxidative stress is a known indication of chronic inflammation [26,27]. Similarly, several purine degradation metabolites were significantly altered between the study cohorts ( Figures 3A and 3B).…”
Section: Inflammationmentioning
confidence: 83%
“…6) In previous studies of GCF, signi cant di erences in the quantities of observed metabolites between the healthy, gingivitis, and periodontitis sites were reported. 7) Many metabolites associated with in ammation, oxidative stress, tissue degradation, and bacterial metabolism were found to be signi cantly elevated in periodontal disease and reduced by toothbrushing with triclosan-containing dentifrice. 8) Metabolomic analysis of saliva in diabetics replicated the metabolite signature of periodontal disease progression in non-diabetic patients and revealed unique metabolic signatures associated with periodontal disease in diabetics.…”
Section: Introductionmentioning
confidence: 99%